Working out the plans in a system of object positioning inside the building using mobile devices - SALEH, Hadi; ALEXANDROV, Dmitriy (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The system of object positioning inside the building using mobile devicesand points of Wi-Fi access is considered, in particular, its architecture and subsystemof working out of the building plans.